Selective IgA Deficiency and Common Variable Immunodeficiency - Kadri Kamber; Zuhal Karalı; Sara Şebnem Kılıç (Güncel Pediatri, 2009)
Selective IgA deficiency (sIgAD), using 5 mg/dl of serum IgA as the upper limit for diagnosis and concomitant lack of secretory IgA, is the most common form of primary immunodeficiency. The pathogenesis of IgA deficiency is not known, although abnormalities in Ig class switching and the cytokines involved in isotype switching have been implicated. Common Variable Immunodeficiency (CVID) is a heterogenous group of B cell deficiency syndromes characterized by hypogammaglobulinemia, impaired antibody production and recurrent bacterial infections. Defective T-cell activation may lead to an impairment in cognate T-B-cell interaction due to impaired expression of CD40 ligand and/or abnormalities in the production of T-cell-derived cytokines required for fully functional B-cell activation, proliferation and/or differentiation which could indeed explain the impairment in antibody production present in CVID patients. It has been found that cytokines are produced in low levels due to the decreased T cell function which occurs as a result of the defect in CD40L expression in CVID patients. (Journal of Current Pediatrics 2009; 7: 90-5)